Quantifying the Potential of the Xtract Heatsaver System to Enhance Thermoregulation and Prevent Hypothermia in Combat Casualties. (September 2022) - Lavender, Steven A.; Kachlan, Anas; Pennells, Simon; Spence, David
Conductive or convective heat loss is a serious concern in combat casualties that are an enhanced risk of hypothermia due to shock and environmental exposures. Eleven subjects participated in repeated measures study designed to assess whether alternative hypothermia prevention systems can retain body temperatures better in a cold environment than the currently fielded solution. Results showed that when the subjects were using the new Xtract Heatsaver System there was significantly less change in the body's core temperature and less thermal discomfort as compared with the currently field Hypothermia Prevention and Mitigation Kit.